Strategy for SMA Muhammadiyah 3 Pandaan in Learning during the Covid-19 Pandemic - Desi Intan Romadhona; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The study discusses the training a teacher does to the student in imposing an online learning in Muhammadiyah 3 Pandaan High Schools. It needs to be researched, since the value of learning is a course of action that includes the use of methods and the use of various power resources in learning. Where learning is the effort of educators to help learners engage in learning activities, thus developing a new territory in learning strategy to be effective and efficient. Strategy may be defined as a broad outline of course to act in an effort to achieve the established goals of teacher and learner's activities in the realization of teaching activities to achieve the outlined goals. According to the covid-19 strategy of learning, it is hoped to provide increased progress in the effective teaching learning activities that each learning takes place. So in boosting good qualities, it is expected that learners are more active to ask questions, be more active in discussions, and be more active in sharpening their new knowledge. The learning strategy influences what they gets and what's inside.